Peran Strategis Inspektorat dalam Mewujudkan Tata Kelola Pemerintahan yang Baik dalam Pengelolaan Keuangan Komisi Pemilihan Umum - Muhammad Abdillah Faqih Mardiansyah; Erwin Irawan; Kalvin Yulnex Maniani; Ahmad Nur Hidayat (Indonesian Accounting Literacy Journal, 2026)
This study aims to analyze the strategic role of the Inspectorate in realizing good governance, particularly in financial management at the General Elections Commission (KPU). Furthermore, it identifies supporting and inhibiting factors and formulates strategies to strengthen the Inspectorate's role. This study uses a descriptive qualitative approach to deeply understand the social dynamics of institutional structures, governance values, and oversight practices in the context of a complex public organization such as the KPU. Data collection was conducted through semi-structured interviews, participant observation, and documentation studies. The results show that the Inspectorate has a strategic role, shifting from mere administrative compliance to a proactive mechanism that ensures public accountability, transparency, and institutional integrity. Its main contributions include strengthening financial accountability through risk-based audits and acting as an 'integrity guardian' to prevent bureaucratic corruption.